TRIM25 inhibits influenza A virus infection, destabilizes viral mRNA, but is redundant for activating the RIG-I pathway. Issue 12 (23rd June 2022) - Choudhury, Nila Roy; Trus, Ivan; Heikel, Gregory; Wolczyk, Magdalena; Szymanski, Jacek; Bolembach, Agnieszka; Dos Santos Pinto, Rute Maria; Smith, Nikki; Trubitsyna, Maryia; Gaunt, Eleanor; Digard, Paul; Michlewski, Gracjan
Abstract: The E3 ubiquitin ligase TRIM25 is a key factor in the innate immune response to RNA viruses. TRIM25 has been shown to play a role in the retinoic-acid-inducible gene-1 (RIG-I) pathway, which triggers expression of type 1 interferons upon viral infection. We and others have shown that TRIM25 is an RNA-binding protein; however, the role of TRIM25 RNA-binding in the innate immune response to RNA viruses is unclear. Here, we demonstrate that influenza A virus (IAV A/PR/8/34_NS1(R38A/K41A)) infection is inhibited by TRIM25. Surprisingly, previously identified RNA-binding deficient mutant TRIM25ΔRBD and E3 ubiquitin ligase mutant TRIM25ΔRING, which lack E3 ubiquitin ligase activity, still inhibited IAV replication. Furthermore, we show that in human-derived cultured cells, activation of the RIG-I/interferon type 1 pathway mediated by either an IAV-derived 5′-triphosphate RNA or by IAV itself does not require TRIM25 activity. Additionally, we present new evidence that instead of TRIM25 directly inhibiting IAV transcription it binds and destabilizes IAV mRNAs. Finally, we show that direct tethering of TRIM25 to RNA is sufficient to downregulate the targeted RNA. In summary, our results uncover a potential mechanism that TRIM25 uses to inhibit IAV infection and regulate RNA metabolism.